Implementasi Kontrol Proportional - Integral Pada Bidirectional Converter Untuk Sistem Pengisian Baterai Turbin Angin - Hamlah Nadela Ilif Baridatul Jannah; Herman Hariyadi (Journal of Applied Smart Electrical Network and Systems, 2021)
The level of demand for electrical energy in Indonesia is currently getting higher and will continue with the increase in population so that it is required to conduct research in the field of renewable energy. To be able to support renewable energy research, a switching circuit is needed for the battery charging system. The switching circuit used is a converter bidirectional circuit controlled by an Arduino Uno microcontroller based on PI (Proportional-Integral) control. PI control functions to regulate the voltage so that it has a stable output voltage value. From the research results of the Konverter bidirectional circuit, using trial and error control constants Kp: 2,6 and Ki: 5,6, it was found that the battery charging time was obtained with an initial voltage of 22.9 Volt to 24 Volt battery without using PI control, which was 6 hours 57 minutes, whereas if using the PI control with Kp: 2,6 and Ki: 5,6 with the initial battery voltage of 22.9 Volt to 24 Volt, the battery charging becomes faster, which is 2 hours 45 minutes.